Normal High HbA1c a Risk Factor for Abnormal Pain Threshold in the Japanese Population - Chieko Itabashi; Hiroki Mizukami; Sho Osonoi; Kazuhisa Takahashi; Kazuhiro Kudo; Kanichiro Wada; Wataru Inaba; Guo Danyang; Chiaki Uchida; Chiaki Uchida; Satoko Umetsu; Satoko Umetsu; et al. (Frontiers in Endocrinology, 2019)
Purpose: Small fiber dysfunction is common in subjects with diabetic polyneuropathy (DPN). It is unsettled, however, whether marginal glucose intolerance is implicated in the onset and progression of small fiber dysfunction. Herein, we explored the relationship between glycated hemoglobin levels (HbA1c) and pain sensation in the Japanese population.Methods: A population-based study of 894 individuals (352 men, 542 women; average age 53.8 ± 0.5 years) and 55 subjects with impaired fasting glucose (IFG) in the 2017 Iwaki project were enrolled in this study. Individuals with diabetes were excluded. Relationships between pain threshold for intraepidermal electrical stimulation (P-IES) and parameters associated with metabolic syndrome were examined.Results: P-IES was elevated with increasing of age in women but not in men. Average P-IES (mA) was increased in IFG subjects (n = 55, 0.20 ± 0.03) compared with normoglycemic/non-IFG individuals (n = 894, 0.15 ± 0.01) (p < 0.01). It was comparable between IFG and a group of normal high HbA1c (5.9–6.4%). Univariate linear regression analyses showed no influence of sex, triglyceride, or cholesterol on the value of P-IES. In contrast, there were significant correlations between P-IES and serum HbA1c level (ß = 0.120, p < 0.001) Adjustments for the multiple clinical measurements confirmed positive correlation of P-IES with HbA1c (ß = 0.077, p = 0.046).Conclusion: Individuals with normal high HbA1c exhibited an elevated P-IES in a healthy Japanese population which may be useful for the screening of subclinical DPN.